TANTANGAN MENGHAYATI PANCASILA SEBAGAI FONDASI PENDIDIKAN INDONESIA DAN PERWUJUDANNYA DALAM PENDIDIKAN ABAD-21 - Tentua, Frando A; Serpara, Henderika; Wenno, Eldaa Crystle (Jurusan Pend. MIPA FKIP Universitas Pattimura, 2024)
This study aims to describe the challenges that exist in implementation Pancasila as the foundation of Indonesian education in relation to the entity and identity of the Indonesian nation as well as the realization of the Pancasila Student Profile at SMP Negeri 4 Ambon. This research type is qualitative descriptive research using observation sheets, interview guides and documentation methods. Based on the results of the research conducted, the challenges in implementing Pancasila as the foundation of education are that there are several teachers who have not implemented character cultivation through integrating the Pancasila Student Profile in learning, have not integrated technology as a from of 21st century learning, less than optimal parental involvement in education, the impact foreign culture and technology as well as the influence of student’s interaction. The realization of the Pancasila Student Profile in 21st century education is already running as it should at SMP Negeri 4 Ambon. This can be seen in the daily lives of students at school by carrying out the dimensions of the Pancasila Student Profile namely: (1) having faith, being devoted to God Almighty, and having noble character, (2) global diversity, (3) working together, (4) independent, (5) critical thinking and (6) creative.